Cover Crop Complements Flue Gas Desulfurized Gypsum to Improve No-till Soil Quality. Issue 9 (15th May 2021) - Islam, Khandakar R.; Roth, Greg; Rahman, Mohammad A.; Didenko, Nataliia O.; Reeder, Randall C.
ABSTRACT: Integration of flue gas desulfurized gypsum (FGD-gypsum) with cover crops is expected to improve soil quality (SQ). Our objectives were to evaluate the impact of FGD-gypsum and rye on SQ and the contribution of core indicators to account for SQ variability in a rainfed corn-soybean system. A completely randomized design (CRD) with two FGD-gypsum rates (control vs. 1, 120 kg/ha) x two cover crops (control vs. rye) was conducted. Results showed that both FGD-gypsum and cover crop variably affected soil properties; however, their impact on SQ was more pronounced when integrated. Soil bio-efficiency increased via a large microbial biomass (SMB) pool and higher enzyme activities with a decrease (38%) in microbial catabolism (qCO2 ). Soil chemical balancing increased 15% by active carbon (AC), 26% by active nitrogen (AN), 50% by particulate organic carbon (POC), 58% by particulate organic nitrogen (PON) and 53% by particulate organic phosphorus (POP) contents. Improved physical stability increased aggregate stability (>250 µm) contributed to higher POC, PON, and POP enrichment within aggregates. The increased bio-efficiency, chemical balancing, and physical stability as impacted by FGD-gypsum and cover crop consequently improved SQ. Principal components analysis (PCA) identified eight indicators to calculate for minimum dataset SQ index (SQIMDS ), which explained for 86% of the variability in generalized SQI (SQIgen ). A lack of non-significant difference between SQIg and SQIMDS suggesting that SQIMDS can be consistently used to quantify, compare, and predict SQ. A greater use of FGD-gypsum with cover crops will be important for proactive recycling of industrial by-products for growing crops.